Gerakan Anti-hadis di Media Elektronik: Kassim Ahmad - Nik Zulaikha binti Zulkifli; Nur Fatin Aliah binti Nordin; Nurul Husna Amani binti Mohd Abduh; Maisarah Saidin (Academic Inspired Network, 2024)
Non-Indexed Publication